Linguistic Approach in the Qur’an Al-I‘jāz al-Bayānī - Madlubur Rhisky; Muhammad Eko Arief Wijaksono (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
This study examines al-i‘jāz al-bayānī of the Qur’an through a linguistic approach in order to demonstrate how linguistic features function as a core element of Qur’anic inimitability. Employing qualitative library research, the study analyzes primary Qur’anic texts alongside classical and contemporary scholarly works using descriptive-analytical methods. Linguistic analysis is conducted by integrating semantic, syntactic, and discourse-based perspectives to uncover the relationship between form and meaning in Qur’anic language. The findings reveal that Qur’anic al-i‘jāz al-bayānī is systematically manifested through three interrelated linguistic dimensions. First, lexical precision (ikhtiyār al-alfāẓ) produces a high degree of semantic density, enabling the Qur’an to convey complex theological and moral meanings with remarkable brevity and accuracy. Second, syntactic arrangement (naẓm) demonstrates a harmonious integration between grammatical structure and intended meaning, confirming that Qur’anic syntax functions as a meaning-driven and rhetorically purposeful system. Third, the rhetorical and discursive function of Qur’anic language highlights its persuasive power and communicative effectiveness, engaging readers cognitively, emotionally, and spiritually across diverse contexts. This study concludes that al-i‘jāz al-bayānī is not merely an aesthetic phenomenon, but a comprehensive linguistic system in which lexical choice, syntactic structure, and discourse strategies operate cohesively. By applying linguistic analysis, the study contributes to a more academically rigorous understanding of Qur’anic inimitability and strengthens the integration between classical Islamic scholarship and contemporary linguistic studies.